Compliance with the Use of Mask in Young Adult Community Group in Kupang City - Basy, Angel Yulied; Umbu Roga, Anderias; Weraman, Pius; Ratu, Jacob M.; Lada, Christina Olly (International Journal Labs, 2022)
Background: COVID-19 is a deadly disease transmitted by the SARS-CoV-2 virus that spreads quickly and widely through droplets and the air. Prevention behavior through the 3M, namely maintaining distance, washing hands with soap, maintaining distance, and always using a mask when doing activities outside the home, is important for every individual. Community compliance with Government appeals is very important in controlling the increasing number of cases. Aim: This study aims to analyze the simultaneous influence of knowledge, attitudes, social support, income, education, employment, and history of the COVID-19 vaccine to obtain a model of factors that influence adherence to the use of masks during the COVID-19 pandemic in adolescent in Kupang City. Method: This study is an analytic observational study with a cross-sectional design. The research sample was young adults with an age range of 20-40 years as many as 395 people. Data were collected using a list of questions and observations. Data analysis using multiple logistic regression. Findings: The results of statistical analysis show that there is a significant effect between attitudes, social support, employment, and history of administering the COVID-19 vaccine with adherence to the use of masks. With the regression equation model g(x)=2.582+-2.521 (social support) +-3.222 (occupation) +-6.136 (vaccine history) with adherence to the use of masks. Occupation is the dominant variable, with a magnitude of 25,082 times its effect on compliance with the use of masks. Immediate actions taken by the government and relevant stakeholders are firstly increasing public knowledge through continuous health promotion about the dangers of COVID-19 and secondly increasing vaccination, and tightening community mobilization’s supervision.